Isolation and Characterization of Plant Growth-Promoting Rhizobacteria from Coffee Plantation Soils and Its Influence on Maize Growth - Yasin Ahmed Waday; Ermias Girma Aklilu; Mohammed Seid Bultum; Venkata Ramayya Ancha; Dejene Beyene (Applied and Environmental Soil Science)
Plant growth-promoting rhizobacteria (PGPR) are an important bacterial resource as biofertilizers, which can promote plant growth and increase crop yields. In this study, isolation, characterization, and its effect on plant promotion were assessed by isolating PGPR using soil samples collected from Jimma, Ethiopia. Out of 10 isolates, three of them (JEC3, JEC4, and JEC7) exhibited PSB traits in Pikovskaya media by solubilizing phosphate and producing IAA. Of the three isolates, JEC4 recorded the maximum phosphate solubilization index (4.98), soluble phosphate (283 μg/ml), and IAA production (10.21 μg/ml). The findings of the isolates' morphological and biochemical tests showed that JEC3, JEC4, and JEC7 as Bacillus sp., Pseudomonas sp., and Enterobacter sp., respectively. The optimization of phosphate solubilization was done using different incubation times and sources of carbon and nitrogen. Furthermore, the isolate (JEC4) was tested for plant growth-promoting (PGP) activities and indicated the production of ammonia, hydrogen cyanide, and siderophore. JEC4 isolate showed a significant increase in sideways (%) seed germination, root and shoot length, fresh and dry weight of root, and shoot of maize in field experiments than the untreated ones. The results indicate that the JEC4 isolate can be developed as a biological fertilizer for promoting crop productivity and ecosystem dynamics.